2002
DOI: 10.1148/radiol.2243011085
|View full text |Cite
|
Sign up to set email alerts
|

Idiopathic Chronic Pancreatitis in Children: MR Cholangiopancreatography after Secretin Administration

Abstract: Secretin improves the sensitivity of MR cholangiopancreatography in diagnosing early-onset idiopathic chronic pancreatitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
25
0
4

Year Published

2003
2003
2021
2021

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(29 citation statements)
references
References 21 publications
0
25
0
4
Order By: Relevance
“…In children < 6 years, it is usually only possible to perform MRCP under general anesthesia 64,118 .…”
Section: /B Full Agreement)mentioning
confidence: 99%
See 1 more Smart Citation
“…In children < 6 years, it is usually only possible to perform MRCP under general anesthesia 64,118 .…”
Section: /B Full Agreement)mentioning
confidence: 99%
“…One study performed in children showed that the intravenous application of secretin resulted in a better demonstration of pancreatic side branches 118 . ERCP can safely be performed in children with a pooled complication rate of about 6%, paralleling adults 65,66,[122][123][124][125][126][127] .…”
Section: (Grade 1/b Full Agreement)mentioning
confidence: 99%
“…Elsősorban a kalcifi káció megítélésére és fi nomtű-aspirációs mintavételre alkalmazandó [25,26,37,39,40].…”
Section: Végezhető-e Endoszkópos Ultrahang Gyermekkorban? Endoszkóposunclassified
“…(GRADE 2/C, teljes egyetértés) Megjegyzés: Egy gyermekeken végzett tanulmány azt is bizonyította, hogy az intravénásan alkalmazott szekretin adása jobb leképezést tesz lehetővé a pancreasvezeték oldalágainak ábrázolására [25,40].…”
Section: Végezhető-e Endoszkópos Ultrahang Gyermekkorban? Endoszkóposunclassified
“…With respect to the possible administration of secretin for better visualization of the pancreatic ducts in MRCP, there are no definitive statements and recommendations in the guidelines due to a lack of comparative prospective literature in adults [18 -21]. The administration of secretin is only recommended in the diagnosis of pediatric patients to increase the diagnostic relevance of MRCP on the basis of two publications [21,22]. Based on the currently available studies and socioeconomic aspects, sonography should therefore be performed first in the case of suspicion of chronic pancreatitis.…”
mentioning
confidence: 99%